(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2022)
The research seeks to identify how to achieve customer loyalty by employing companies for responsive marketing activities, that is, their response to consumers’ needs and desires, to achieve their satisfaction and then achieve loyalty. The field of design, innovation, and creativity, so the aim of the research lies in identifying the concepts of responsive marketing and customer loyalty and the relationship between them, because of its great importance in light of modern marketing trends, including the search for the latent needs and desires of consumers and achieving them by meeting them. To achieve the goal, a number of hypotheses were formulated, including that there is a significant correlation between responsive marketing in its dimensions and customer loyalty, as well as a significant effect of responsive marketing in achieving customer loyalty. The analytical descriptive approach was used through the use of the questionnaire tool, and the five-point Likert scale was used in this, and it was distributed to the individuals surveyed in the Vana Home and Office Furniture Company in the cities of Mosul and Erbil, and a number of statistical methods were used to extract the results from arithmetic means, frequencies and percentages, as well as On the measurement of correlation and influence relations by extracting the values ??of the simple, ordinal, regression coefficient of determination, the values ??of the coefficient of determination R2, the value of f, t and the degrees of freedom, and the research concluded a review of the most important conclusions, including: that responsive marketing fulfills the latent needs and desires of consumers, as well as competitive competition and achieving competitive advantage, and in light of Conclusions A number of proposals have been formulated, the most important of which are: The producing and marketing companies should identify the needs and desires of consumers through studying the market and competitors and collecting the necessary data that would enhance the position of the researched companies in the market and gain the largest possible number of consumers. Keywords: responsive marketing, customer loyalty